2002
DOI: 10.1093/geronb/57.6.p510
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation in Very Old Age: Cross-Sectional and Longitudinal Findings From BASE

Abstract: Social participation, defined as socially oriented sharing of individual resources, is often regarded as an important criterion of quality of life in old age. We distinguished three types of participation with respect to content, context, and resources required to participate: collective, productive, and political participation. Data from the multidisciplinary Berlin Aging Study were used to describe social participation of a very old population and to examine individual differences and changes over time. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
201
0
28

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(241 citation statements)
references
References 14 publications
12
201
0
28
Order By: Relevance
“…In agreement with many studies [2,[23][24][25][26][27][28][29][30], younger age and the absence of recent stressing events contributed to best explain a higher accomplishment level of social participation, while better self-perceived health best explained greater satisfaction with social participation. Stressing events can impede social participation.…”
Section: Best Correlates Of Accomplishment Level and Satisfaction Witsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with many studies [2,[23][24][25][26][27][28][29][30], younger age and the absence of recent stressing events contributed to best explain a higher accomplishment level of social participation, while better self-perceived health best explained greater satisfaction with social participation. Stressing events can impede social participation.…”
Section: Best Correlates Of Accomplishment Level and Satisfaction Witsupporting
confidence: 90%
“…Moreover, to our knowledge, no study aimed at identifying the correlates of satisfaction with social participation. Correlates of accomplishment level of social participation identified in the literature [2,[23][24][25][26][27][28][29][30][31][32] are personal factors such as gender, age, and education; health status and impairment (including disease category, comorbidity, self-perceived health, and wellbeing); level of activity; and physical and social environment. With the same participants, identifying the variables that best explain accomplishment level and satisfaction with social participation can help to better understand the specificity of these two concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In their analysis of social participation, Bukov et al (2002) proposed, among other dimensions, that social activities may be classified as self-oriented activities (when the individual receives resources from the social environment) or socially oriented activities (when the individual contributes resources to the social environment). Taking these dimensions into account, it is possible to identify three different types of active aging activities: (1) self-oriented activities involving low investment, (2) self-oriented activities involving high investment, and (3) socially oriented activities which, by nature, tend to involve a high investment.…”
Section: Membership In Political Organizations and Active Aging Activmentioning
confidence: 99%
“…One longitudinal study showed that, unlike men, the frequency of women's involvement in leisure activities was less affected by decreased health. 40 Such differences might be explained by prior social participation habits, 41 meaning of social activities 42 , different obligations and relevance of environmental factors. In the present study, more women lived alone and were single or widowed, they might have more social obligations (e.g.…”
Section: Perceived Proximity To Neighborhood Resources As a Moderatormentioning
confidence: 99%